2021
DOI: 10.1088/1741-4326/abe98b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of collisionality on turbulence in the edge of tokamak plasma using 3D global simulations

Abstract: Collisionality is one of the key parameters in determining turbulent transport in the plasma edge, regulating phenomena such as "shoulder formation", separation of scale lengths in the scrape-off layer, turbulence damping and zonal flow dynamics. Understanding its role is therefore of primary importance for future reactors like ITER. Obtaining reliable predictions and a better characterization of plasma flow properties when varying collisionality remains, however, a critical challenge for the simulations. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 97 publications
0
25
0
Order By: Relevance
“…Whereas GRILLIX used the Braginskii values for resistivity and heat conductivities directly, relaxed parameters were used in GBS (η increased by factor 3 and χ ,e,i reduced by factor between 4.8 (at the targets) and 20 (at the OMP)) and TOKAM3X (η increased by factor 1.8 and χ ,e,i reduced by factor 1.8) in order to reduce computational costs and improve the numerical stability. Previous studies have indicated that artificially increased collisionality leads to broadened SOL profiles [13], [15], larger blobs and higher fluctuation levels [13]. Increased resistivity can directly affect the plasma potential (affecting the scale of potential fluctuations and the magnitude of the E × B transport) [13], extend the inertial regime of SOL blobs [69] and change the position where blobs are generated [70].…”
Section: Impact Of Relaxed Parametersmentioning
confidence: 99%
See 4 more Smart Citations
“…Whereas GRILLIX used the Braginskii values for resistivity and heat conductivities directly, relaxed parameters were used in GBS (η increased by factor 3 and χ ,e,i reduced by factor between 4.8 (at the targets) and 20 (at the OMP)) and TOKAM3X (η increased by factor 1.8 and χ ,e,i reduced by factor 1.8) in order to reduce computational costs and improve the numerical stability. Previous studies have indicated that artificially increased collisionality leads to broadened SOL profiles [13], [15], larger blobs and higher fluctuation levels [13]. Increased resistivity can directly affect the plasma potential (affecting the scale of potential fluctuations and the magnitude of the E × B transport) [13], extend the inertial regime of SOL blobs [69] and change the position where blobs are generated [70].…”
Section: Impact Of Relaxed Parametersmentioning
confidence: 99%
“…In this section we first provide a brief introduction of the models in each of the codes, and then discuss the choice of sources and parameters to model the TCV-X21 scenario. For the complete physical models (excluding boundary conditions) of the respective codes, the reader is directed to Giacomin and Ricci, 2020 [51] for GBS, appendix A of Zholobenko et al, 2021 [20] for GRILLIX, and Tatali et al, 2021 [13] for TOKAM3X. For a discussion of the sheath boundary conditions used in this study, see Sec.4.1 and appendix A.…”
Section: Simulation Codesmentioning
confidence: 99%
See 3 more Smart Citations